Kepentingan Amerika Serikat dan Prancis dalam Intervensi Kemanusiaan di Libya pada Tahun 2011 - Adhika Isthianto Utomo; Reni Windiani (Journal of International Relations Diponegoro, 2018)
United States and France were the two countries that had high involvement in humanitarian intervention in Libya in 2011. In fact, the humanitarian intervention process was deviated from the original goal of humanitarian intervention which was for humanitarian reasons. This indicates that the United States and France have their own interests behind humanitarian intervention in Libya. This research aims to analyze the interests of the United States and France in carrying out humanitarian intervention in Libya in 2011. In this study also briefly explained how the conflict in Libya occur until the UN Security Council gave a decision to intervene. This study uses qualitative and explanatory research methods with two data sources, primary and secondary data. The theoretical framework used in this research is Neorealism theory. From the research that has been done, there are three interests of the United States and France in carrying out humanitarian intervention in Libya. The First is the interests of the United States and France to control oil in Libya, and the second is the political factor of the United States and France, and the third is the interest of the United States to overthrow the Muammar Gaddafi regime.